2005
DOI: 10.1111/j.1475-1313.2004.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive phakometric measurement of corneal and crystalline lens alignment in human eyes

Abstract: We describe a non-invasive phakometric method for determining corneal axis rotation relative to the visual axis (beta) together with crystalline lens axis tilt (alpha) and decentration (d) relative to the corneal axis. This does not require corneal contact A-scan ultrasonography for the measurement of intraocular surface separations. Theoretical inherent errors of the method, evaluated by ray tracing through schematic eyes incorporating the full range of human ocular component variations, were found to be larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…We believe that the main reason for the different dominance between ocular and corneal HOAs may be that the optical axis of the cornea is not coaxial with that of the lens, as has been suggested previously. 17 In that case, spherical aberrations of the cornea or lens can be asymmetric aberrations in the other optical system. Our results showed that there was an effect due to the axes of measurements in a wavefront analysis, at least in normal subjects and in patients following conventional LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the main reason for the different dominance between ocular and corneal HOAs may be that the optical axis of the cornea is not coaxial with that of the lens, as has been suggested previously. 17 In that case, spherical aberrations of the cornea or lens can be asymmetric aberrations in the other optical system. Our results showed that there was an effect due to the axes of measurements in a wavefront analysis, at least in normal subjects and in patients following conventional LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…A 14°tilt around the vertical axis of the crystalline lens would theoretically give this amount of RA 50 (p.209) . Actually, the tilt of the crystalline lens is much smaller 72,73 , which points to the posterior corneal surface as the source of the RA. Both anterior and posterior corneal surfaces have the same principal meridians 74 .…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Phakometry is a noninvasive technique for measurement of the crystalline lens radii of curvature, usually involving photography of the Purkinje-Sanson images [37]. It has now been over a century since Tscherning devised the ophthalmophakometer for the purpose of measuring and determining the spherical radii of ocular surfaces, the depths or thickness of ocular structures and their degree of alignment to an optical axis [38].…”
Section: Phakometrymentioning
confidence: 99%